An integrated online platform for cryptographic analysis of substitution boxes and image encryption metrics - Aydin, Yilmaz; Ozkaynak, Fatih (Springer London Ltd, 2026)
The study's primary focus is on the design and implementation of an integrated online analysis platform. This platform can perform cryptographic analysis of S-boxes. The S-Box is considered a fundamental building block of block cipher algorithms. The study also focuses on testing metrics used in image encryption processes. Comprehensive analyses supported by critical metrics such as Nonlinearity, SAC, BIC, DDT, histogram analysis, correlation, NPCR, UACI, PSNR, and SSIM have been provided by bringing together test tools scattered throughout literature. The application provides users with flexible data entry, visualization, and reporting capabilities via a robust web interface. The proposed system has analyzed S-box structures generated using classical and chaotic systems. It has also been comparatively evaluated with various modern block cipher structures, including the AES algorithm. The developed encryption algorithm combines zigzag reading, spiral transformation, S-box manipulation, and XOR operations to provide encrypted images with high randomness, low correlation, and statistical resilience. Results demonstrate the system's effectiveness in academic research and applied cybersecurity.
Keywords: S-box analysis; Image encryption; Cryptography; Online evaluation tool